Evaluating Pellet and Meal Feeding Regimens on Finishing Pig Performance, Stomach Morphology, Carcass Characteristics, and Economics - J. A. De Jong; J. M. DeRouchey; M. D. Tokach; S. S. Dritz; R. D. Goodband; M. Allerson (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 2,100 pigs (PIC 327 × 1050, initially 68.8 lb) were used in a 118-d trial to determine the effects of pellet feeding regimens on finishing pig growth performance, stomach morphology, and carcass characteristics. Pens of pigs were balanced by initial BW and randomly allotted to 1 of 6 dietary treatments (14 pens/treatment with 25 pigs/pen). Pens were sorted by gender allowing for 7 barrow and 7 gilt pens/treatment. The same corn-soybean meal–based diets containing 15% dried distillers grains with solubles were used for all treatments and fed in 5 phases. The 6 treatments included a meal or pelleted diet fed from d 0 to 118, a meal diet fed from d 0 to 70 and then pellets from d 70 to 118, a pelleted diet fed from d 0 to 70 and then meal from d 70 to 118, or pellets and meal rotated every two weeks starting with meal or pellets. On d 110, 4 pigs from each pen were harvested with the stomachs collected and a combined ulcer and keratinization score determined for each pig. Overall, there were no differences (P>0.956) for ADG across feeding regimens. Pigs fed meal throughout had the greatest (P<0.05) ADFI, while pigs fed pellets throughout had the lowest (P<0.05), with all other treatments intermediate (P<0.05). Pigs fed pelleted diets throughout had the most improved (P<0.05) F/G, while pigs fed meal throughout had the worst F/G (P<0.05), with all other treatments intermediate (P<0.05). When pelleted diets were fed for the last 48 d, or for the entire trial, the incidence of ulceration and keratinization increased (P<0.05), while pigs fed meal for the last 48 d had lower incidence (P<0.05), with all other treatments intermediate (P<0.05). Feeding pellets throughout increased (P<0.05) the number of pigs removed per pen compared to all other treatments. Removals were determined by an onsite farm manager as animals unable to remain in the general population due to health or welfare problems. There were no differences (P>0.10) for any carcass characteristics measured. For economics, feeding a meal diet throughout the experiment increased (P<0.05) feed cost/lb gain compared to all other treatments. There were no significant differences (P>0.10) for IOFC; however, numerical differences showed that rotating between a pellet and a meal diet improved IOFC by 1 to 2 above feeding a meal diet throughout the finishing period. In conclusion, feeding pelleted diets improved F/G but increased stomach ulceration and removals; however, rotating pellets and meal diets provided an intermediate F/G response without increasing in stomach ulceration and subsequent removals compared to only feeding pelleted diets.
Keywords: finishing pig; meal; pellet; ulcer